Bioenergeticeskie kriterii normirovanija trenirovocnych nagruzok i special'noj rabotosposobnosti plovcov vysokogo klass - Vojtenko, Ju. L.; Solomatin, V. R. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
The present study was conducted with the aim of developing an integrated monitoring system for the level of development of bioenergetic abilities of swimmers on the basis of tests in standardized laboratory tests. The influence of bioenergetic factors on the level of sporting achievements varies depending on the capacity and duration of the exercise. The results at distances of 400, 800 and 1500 m have the greatest correlation with the maximum aerobic capacity and capacity. The indicators of maximum anaerobic glycolytic capacity, capacity and efficiency are significant at a distance of 50 to 200 m. Continuous monitoring of the state of special working capacity is a necessary prerequisite for effective management of the training process for elite swimmers.